A comparison of human immunodeficiency virus, hepatitis C virus, hepatitis B virus, and human T‐lymphotropic virus marker rates for directed versus volunteer blood donations to the American Red Cross during 2005 to 2010. Issue 6 (25th September 2012) - Dorsey, Kerri A.; Moritz, Erin D.; Steele, Whitney R.; Eder, Anne F.; Stramer, Susan L.
<x xml:space="preserve">Abstract</x> BACKGROUND: At most US blood centers, patients may still opt to choose specific donors to give blood for their anticipated transfusion needs. However, there is little evidence of improved safety with directed donation when compared to volunteer donation. STUDY DESIGN AND METHODS: The percentage of directed donations made to the American Red Cross (ARC) from 1995 to 2010 was determined. Infectious disease marker rates for human immunodeficiency virus (HIV), hepatitis C virus (HCV), hepatitis B virus (HBV), and human T‐lymphotropic virus (HTLV) were calculated for volunteer and directed donations made from 2005 to 2010. Odds ratios (ORs) were calculated to compare marker‐positive rates of directed donations to volunteer donations. RESULTS: The percentage of donations from directed donors declined from 1.6% in 1995 to 0.12% in 2010. From 2005 to 2010, the ARC collected 38, 894, 782 volunteer and 69, 869 directed donations. Rates of HIV, HCV, HBV, and HTLV for volunteer donations were 2.9, 32.2, 12.4, and 2.5 per 100, 000 donations, respectively; for directed, the rates were 7.2, 93.0, 40.1, and 18.6 per 100, 000. After demographics and first‐time or repeat status were adjusted for, corresponding ORs of viral marker positivity in directed versus volunteer donations were not significant for HIV, HBV, or HTLV and significant for HCV (OR, 0.7; 95% confidence interval, 0.50‐0.90). CONCLUSIONS: Directed donations have declined by 92% at the ARC since 1995, but have higher viral marker rates than volunteer donations. The difference can be explained in part by the effects of first‐time or repeat status of the donors. Patients considering directed donation should be appropriately counseled about the potential risks.